1997
DOI: 10.1021/tx960129f
|View full text |Cite
|
Sign up to set email alerts
|

A Refined Substrate Model for Human Cytochrome P450 2D6

Abstract: Cytochromes P450 (P450s) constitute a large superfamily of heme-containing enzymes, capable of oxidizing and reducing a variety of substrates. Cytochrome P450 2D6 is a polymorphic member of the P450 superfamily and is absent in 5-9% of the Caucasian population as a result of a recessive inheritance of gene mutations. Recently, the importance of aspartic acid 301 (Asp301) for the catalytic activity of P450 2D6, as indicated by a preliminary homology model, was confirmed by site-directed mutagenesis experiments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…Site directed mutagenesis experiments indicate that Asp301 is the negatively charged amino acid responsible for binding to the substrate nitrogen. 8 In addition, also Ser304, Thr309 and Val370 appear to be involved in substrate binding 9 although further models are required for confirmation.…”
Section: General Characteristics Of Cyp2d6mentioning
confidence: 99%
“…Site directed mutagenesis experiments indicate that Asp301 is the negatively charged amino acid responsible for binding to the substrate nitrogen. 8 In addition, also Ser304, Thr309 and Val370 appear to be involved in substrate binding 9 although further models are required for confirmation.…”
Section: General Characteristics Of Cyp2d6mentioning
confidence: 99%
“…In drug discovery research it is of great interest to identify whether a compound is a substrate or not, and considerable effort has been put into the development of models to identify substrates and/or inhibitors of CYP2D6. Several pharmacophore models have been published identifying common features in CYP2D6 substrates and inhibitors (Koymans et al, 1992;de Groot et al, 1997de Groot et al, , 1999Lewis et al, 1997). The pharmacophore comprises basic nitrogen atom 5-7 or 10 Å from the site of oxidation, a flat hydrophobic region near the site of oxidation and a negative molecular electrostatic potential coplanar with this hydrophobic region (see examples in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is not surprising to find that CYP2D6 catalyzes the 5-hydroxylation of 1-PP. Pharmacophore modeling found that typical CYP2D6 substrates often contain a cationic nitrogen 5 or 7 Å from their major sites of oxidation, ideally situated to form ion-pair interactions with CYP2D6 active-site aspartic acid (D301) (De Groot et al, 1997). 1-PP would be a preferred CYP2D6 substrate for the ion-pairing orientation.…”
Section: Discussionmentioning
confidence: 99%